The Evaluation of the Views of the Students from Environmental Engineering on Global Warming in Terms of Critical Thinking Trends and Emotional Intelligence Levels - Bahanur Malak Akgün; Necla Balık; Mustafa Akgün (Anı Publishing, 2018)
Aimed to evaluate the evaluation of the views of the students from environmental engineering on global warming in terms of critical thinking trends and emotional ıntelligence levels. According to mixed method's sequential transformational design, 36 students were asked to respond Information Form, California Critical Thinking Disposition (CCTDI-R), Revised Schutte Emotional Intelligence (RSEIS) scales at the quantitative stage. In the pearson correlation analysis, respectively strong, strong, low, moderate positive correlations were found between CCTDI-R total score with RSEIS total score and also sub-dimensions of this scale like optimism/mood state regulation, the use of emotion, evaluation of emotion. At the qualitative stage, 15 students with CCTDI-R scores of low and intermediate level responded to open-ended questions about articles of two different approaches to explain global warming. Themes were obtained through content analysis. Themes are the understanding of whole in searching of truth, open-mindedness, multifactorial assessment of the causes of global warming, the emphasis on the causes of global warming, intervene to global warming. In order to increase students' critical thinking disposition and emotional intelligence level of students, it has been proposed that training programs can be planned.